2020
DOI: 10.3390/catal10010107
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Support Synergy of Supported Gold Nanoclusters in Selective Oxidation of Alcohols

Abstract: Gold catalysts have been reported to exhibit good performance in aerobic oxidation of alcohols, but the intrinsic origin of the catalytic reactivity is still illusive. The catalyst preparation method, the morphology of the gold particles, and even the support might be key factors that determine the activity. Here, we prepared a series of gold catalysts with different supports, i.e., the hydrotalcite (HT), ZnO, MgO, Al2O3, and SiO2, by using the atomically controlled Au25 nanoclusters (NCs) as the gold precurso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…That meant the presence of aldehyde group might promote the hydrogenation of vinyl group on the Au/ZrO2 catalyst. From the results, the Au25/ZnAl-300 catalyst with moderate basicity and acidity [26,42] showed the highest selectivity, which indicated the typical basic or acidic supports might be detrimental to the selectivity for the hydrogenation of CAL to COL in this work.…”
Section: Discussion About the High Selectivity Over The Au25/znal-300mentioning
confidence: 93%
“…That meant the presence of aldehyde group might promote the hydrogenation of vinyl group on the Au/ZrO2 catalyst. From the results, the Au25/ZnAl-300 catalyst with moderate basicity and acidity [26,42] showed the highest selectivity, which indicated the typical basic or acidic supports might be detrimental to the selectivity for the hydrogenation of CAL to COL in this work.…”
Section: Discussion About the High Selectivity Over The Au25/znal-300mentioning
confidence: 93%
“…The color of the composite particles distinctively changed from light pink to brown; this observation could imply the gradual increase of the AuNP loading onto the MPT particles. Although many AuNPs containing nanoscale particles exhibit distinctive surface plasmon resonance (SPR) bands in the visible spectrum [8,9,[33][34][35], these AuNPs incorporated on the MPT particles displayed flat SPRs across the entire wavelength. The near absence of detectable SPRs could be due to the relatively small size of the AuNPs formed within the pores and the scattering characteristics of the MPT host particles [36,37].…”
Section: Resultsmentioning
confidence: 99%
“…Nontoxic metal-based materials have been extensively fabricated to develop reactive catalysts that can be operational in environmentally friendly conditions for various chemical transformation reactions [1][2][3][4][5]. One attractive candidate is a colloidal form of nanoscale metal particles that can be prepared in green solution media (e.g., water and EtOH) and still show catalytic reactivity and recyclability [2,[6][7][8]. Among many metal nanoparticles, gold nanoparticles (AuNPs) have shown ideal characteristics due to their biocompatible nature and well-established preparation strategies for diverse structures [2,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Villa et al reported that the addition of Bi into PdAu/C can significantly improve the selectivity in ODH of benzyl alcohol because Bi blocks partial of active sites and suppress parallel reaction in ODH of benzyl alcohol [18]. In addition to geometric effect, creating metal-metal [15,19], metal-support [20] or metal-organic interfaces [14] to tune the electronic structures of metal nanoparticles is also an important strategy to regulate their adsorption behaviors. Among them, p-electron metal Bi, is frequently used as a modifier to engineer the electronic structure of Pd and Pt as it can donate electrons to these active species and prevent them from being overoxidized [21,22].…”
Section: Introductionmentioning
confidence: 99%